Research on the Regulation and Compliance of ESG Information Disclosure in the Securities Market - Wu, Huihui; Ali, Hasani Mohd; Alam, Hazlina Shaik Md Noor (Journal of Ecohumanism, 2024)
The disclosure of ESG information only depends on the voluntary disclosure of enterprises, which cannot ensure the openness and transparency of public information. Therefore, the supervision of the disclosure of ESG information is particularly important. Although China is gradually strengthening the ESG information disclosure requirements for listed companies, the regulatory framework for ESG information disclosure in China still needs to be optimized due to the differences in localization, small scope of disclosure, and large differences in evaluation system and standard system. This paper analyzes the current situation of ESG information disclosure in China, including the overall disclosure situation, the disclosure characteristics of different enterprises and industries, and the current situation of carbon emissions disclosure. The article points out the problems in the supervision system, such as the imperfection of supervision basis, the singleness of supervision subject and the insufficiency of supervision cooperation mechanism. On this basis, this paper puts forward some suggestions to improve the regulatory basis, build multiple collaboration subjects and optimize the regulatory collaboration mechanism, in order to improve the quality and efficiency of ESG information disclosure and promote the healthy development of China's capital market.